Advances in management of chronic metabolic acidosis in chronic kidney disease. Issue 5 (September 2019) - Chen, Wei; Abramowitz, Matthew K.
Abstract : Purpose of review: Chronic metabolic acidosis is a common complication of chronic kidney disease (CKD) and is associated with adverse consequences, such as CKD progression and muscle wasting. We review the findings from recent clinical trials that have examined the effects of sodium bicarbonate therapy and veverimer in patients with CKD and chronic metabolic acidosis. Recent findings: There are four recent clinical trials on chronic metabolic acidosis of CKD. In a pilot, cross-over study, 6 weeks of sodium bicarbonate therapy improved vascular endothelial function, measured by brachial artery flow-mediated dilation. In a single-center, randomized, open-label study, 6 months of sodium bicarbonate therapy increased muscle mass and lean body mass, and preserved kidney function. The other two clinical trials (phase 1/2 and phase 3 studies) examined the effects of veverimer, which is a hydrochloric acid binder. The phase 3 study showed that 12-weeks of veverimer increased serum bicarbonate levels and might improve physical function. The effects of veverimer on CKD progression, physical function and cardiovascular endpoints as well as its long-term safety are yet to be determined. Summary: Recent studies suggest that sodium bicarbonate therapy may improve vascular endothelial function and muscle mass, and preserve renal function. Veverimer increases serum bicarbonate level and could be a potential new therapeutic option for treating chronic metabolic acidosis.